Exploring Anopheles gut bacteria for Plasmodium blocking activity - Bahia, Ana C (2014)
Malaria parasite transmission requires the successful development of Plasmodium gametocytes into flagellated microgametes upon mosquito blood ingestion, and the subsequent fertilization of microgametes and macrogametes for the development of motile zygotes, called ookinetes, which invade and transverse the Anopheles vector mosquito midgut at around 18-36 h after blood ingestion. Within the mosquito midgut, the malaria parasite has to withstand the mosquito's innate immune response and the detrimental effect of its commensal bacterial flora. We have assessed the midgut colonization capacity of 5 gut bacterial isolates from field-derived, and 2 from laboratory colony, mosquitoes and their effect on Plasmodium development in vivo and in vitro, along with their impact on mosquito survival. Some bacterial isolates activated the mosquito's immune system, affected the mosquito's life span, and were capable of blocking Plasmodium development. We have also shown that the ability of these bacteria to inhibit the parasites is likely to involve different mechanisms and factors. A Serratia marcescens isolate was particularly efficient in colonizing the mosquitoes’ gut, compromising mosquito survival, and inhibiting both sexual- and asexual-stage Plasmodium through secreted factors, thereby rendering it a potential candidate for the development of a malaria transmission intervention strategy.